Design Smart Farming in Rice Field for Monitoring Soil Fertility and Pest Rate Using Internet of Things - Nurdina Widanti; Aditya Alamsyah; Actor Albus; Ahmad Nur Ikhsan; Sri Wiji Lestari; Wike Handini; Sasmito Adi Raharjo (Postgraduate, University of Mataram, 2024)
Rice fields in Indonesia have a strategic role in providing food for the Indonesian population. The Central Statistics Agency (BPS) noted that domestic rice consumption also continues to increase, 98.35% of households in Indonesia consume rice. There are many influencing factors for production rice such as pest, climate change. The aim to optimize rice production by monitoring soil moisture and soil pH and adding protection features to detect rat pests. This tool was built using an Internet of Things-based system integration method, where the system output can be monitored on the blynk and email applications for the reading history of rat pests if they are caught on camera. The results obtained from the system are Soil moisture sensor readings have a system accuracy of 99% with an error value of 0.01. And the pH sensor reading has an accuracy of 99% with an error of 0.015. The most optimal PIR sensor reading is 1 meter and this data is sent simultaneously with the camera sensor via email. Monitoring data on rice agricultural land by adding rat pest protection features, as well as historical data can be captured wellcan provide a strong basis for the development of more effective and sustainable.